Future prospects for hormone replacement therapy. - Reeve, J (1992)
To avoid the complication of osteoporosis, hormone replacement therapy (HRT) is now standard therapy in women with premature ovarian failure. The indications for HRT after the age of 50 are more controversial. There are strong indications from case-control studies that in N. America and Europe HRT protects against osteoporotic fracture, myocardial infarction and stroke; yet the evidence from case control studies is insufficiently precise to quantitate accurately the potential benefits that would accrue from its more widespread use. Clear guidelines also need to be established on the potential usefulness of selective prescribing of HRT using one or more screening procedures. The only effective way of achieving this and of quantitating the potential benefits of HRT with sufficient accuracy is by means of one or more randomized controlled trials. Future research will also address concerns such as the possible increase in the risk of breast cancer after 10 or more years of therapy. Critical to the more widespread acceptance of HRT may be the development of safe regimes which do not promote uterine bleeding as well as minimizing other unwanted side-effects.